Hibridación natural entre Pinus oocarpa y P. pringeli - López Upton, Javier; Velazco Fiscal, Valentín; Jasso Mata, Jesús; Ramírez Herrera, Carlos; Vargas Hernández, J. Jesús (Instituto de Ecología, A.C., 2001)
Natural hybridization between Pinus oocarpa Schiede ex Schlechtendal and P. pringlei Shaw was detected in a sample of 30 individual trees living in simpatry including putative hybrid trees. The area of hybridization is located near Ario de Rosales, Michoacán, México. The canonical discriminant analysis used in the study included a total of 19 morphological and anatomical leaf, cone and seed traits. Trees initially characterized as putative hybrids had intermediate values between parental species for most traits. The number of leaves per fascicle, rows of stomata on the dorsal surface, internal and septal resin canals, peduncle length and cone diameter contributed the most to the canonical discriminant functions and to the separation of the parental species and putative hybrid trees. A second discriminant analysis was performed on samples from 10 trees of P. oocarpa and 7 trees of P. pringlei collected from pure stands outside the area of sympatry and on the data from the 30 trees sampled throughout the sympatric area. In a graphic analysis, trees of every species separated into opposite groups. Furthermore, trees from pure stands were positioned toward the extremes of these groups, indicating a possible process of introgression within the population where hybridization was believed to occur.